2007
DOI: 10.1177/1356336x07076876
|View full text |Cite
|
Sign up to set email alerts
|

The contextual interference effect in applied settings

Abstract: This paper analyses the research literature that approaches the contextual interference effect in applied settings. In contrast to the laboratory settings, in which high interference conditions depress acquisition and promote learning evaluated in retention and transfer tests, in applied settings most of the studies (60%) fail to observe positive effects after manipulation of the contextual interference. Some possible explanations for the fact are hypothesized regarding the characteristics of the task, with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 47 publications
6
54
1
7
Order By: Relevance
“…Barreiros, Figueiredo, and Godinho (2007) showed that the CIE was clearly observed in 29 percent of the studies analysing the acquisition phase (in this situation, performance was better for the grouped than the random schedules). Greater support was found for the retention phase.…”
Section: Field-based Studiesmentioning
confidence: 99%
“…Barreiros, Figueiredo, and Godinho (2007) showed that the CIE was clearly observed in 29 percent of the studies analysing the acquisition phase (in this situation, performance was better for the grouped than the random schedules). Greater support was found for the retention phase.…”
Section: Field-based Studiesmentioning
confidence: 99%
“…Genericamente, as razões apresentadas para que o efeito de IC não possa ser considerado como um fenômeno global de aprendizagem extensível a todas as habilidades motoras estão relacionadas com as características, especificidade e grau de complexidade das tarefas, a organização e quantidade de prática implementada, a estrutura e organização das sessões de prática, o nível de experiência dos aprendizes e os aspectos manipulados (Barreiros, FiGueiredo & Godinho, 2007;Brady, 2008;FiGueiredo, 2004).…”
Section: Amostraunclassified
“…Este fenômeno está relacionado com a influência que a estruturação da prática motora exerce na aprendizagem de habilidades motoras (e.g., Barreiros, FiGueiredo & Godinho, 2007;Brady, 1998;MaGill & hall, 1990).…”
Section: Introductionunclassified
“…Even though the contextual interference effect is still subject of much research (e.g. Boutin & Blandin, 2010;Kantak, Sullivan, Fisher, Knowlton, & Winstein, 2010;Naimo et al, 2013;Porter & Magill, 2010;Wu et al, 2011;Yanci, Reina, Los Arcos, & Camara, 2013), Barreiros et al (2007) pointed out that, by the time, only 42% of the studies were able to observe the effect. These unclear results have driven researchers to investigate whether the effects of contextual interference on motor skills learning would be dependent on factors such as task complexity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the search for these favorable learning outcomes, researchers have been striving to better understand the Contextual Interference Effect, one of the most investigated topics in Motor Learning (Barreiros, Figueiredo, & Godinho, 2007 for a review).…”
Section: Introductionmentioning
confidence: 99%